OPTIMIZING BROILER CHICKEN FARM PRODUCTION USING INTERNET OF THINGS SMART FARM TO REDUCE FOOD LOSS AND WASTE - Karmelia, Anita; Digna, Akira Alpha; Rahma, Alya; Sinaga, Hanif Zaidan; Ramadhani, Anisa Nur (Universitas Ibn Khaldun Bogor, 2024)
In the Broiler Chicken farming industry, Food loss and Waste (FLW) is a big challenge that affects production efficiency and environmental sustainability. The use of Internet of Things (IoT) technology is expected to improve control and monitoring of various aspects of production, from environmental conditions to chicken health, which can ultimately minimize food losses and waste. The method used in this research is a quantitative method, which involves collecting data through direct observation, interviews and distributing questionnaires. Observations were made on broiler chicken farms that had implemented IoT technology. The data collected is then analyzed to understand the impact of using IoT on production efficiency and reducing food loss and waste. The research results show that implementing an IoT technology can significantly increase the operational efficiency of broiler chicken farms. IoT sensors installed at various critical points of the farm help monitor temperature, humidity and air quality conditions, as well as provide real-time information about the health of chickens. With accurate and real-time data, farmers can take preventative action more quickly, thereby reducing the risk of chicken death and food waste. The aim of this research shows that broiler chicken farms that use IoT technology experience improvements in environmental management and chicken health, which contribute to reducing food loss and waste. Broiler chicken productivity also increases due to a more controlled environment and more effective management. In conclusion, the integration of IoT technology in broiler chicken farming production is an effective solution to reduce FLW and increase the sustainability and efficiency of the Broiler Chicken farming industry